2012
DOI: 10.1080/02646838.2012.693910
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, parenting stress, self-efficacy and satisfaction in mothers of infants and young children

Abstract: Background: Fatigue is a common health concern reported by mothers of infants and young children, yet little is understood about how fatigue may impact on parenting. Objective: The aim of the study was to explore the associations between fatigue, parenting self-efficacy (PSE) and parenting satisfaction, where parenting stress mediates this relationship. The moderating influence of several contextual factors was also assessed. Method: A sample of 1022 Australian mothers of children aged 0-6 years completed a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 49 publications
(64 reference statements)
2
65
1
2
Order By: Relevance
“…The major consequence of being an efficacious or confident parent is engaging in appropriate parenting tasks that fosters an environment in which their child can grow and develop with success. 5 Consequences of these beliefs are also associated with better quality of life, 19 improved psychological well-being 32 and greater parenting quality. 23 The consequent of being a confident parent can improve parent psychological well-being, promotes positive interactions with the infant, influences health and development of their child, and buffers against challenging situations, isolation, and maladjustment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major consequence of being an efficacious or confident parent is engaging in appropriate parenting tasks that fosters an environment in which their child can grow and develop with success. 5 Consequences of these beliefs are also associated with better quality of life, 19 improved psychological well-being 32 and greater parenting quality. 23 The consequent of being a confident parent can improve parent psychological well-being, promotes positive interactions with the infant, influences health and development of their child, and buffers against challenging situations, isolation, and maladjustment.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 16,18 assessed global self-efficacy beliefs rather than domain general or specific parenting beliefs because they believed it would provide a more comprehensive understanding of parenting confidence when a child has a health condition or disability, whereas domain general or specific measures are tailored to specific issues (e.g., academic performance, obesity, autism, or diabetes management or populations (e.g., adolescents, early childhood, or first time parents). The measure used most often (n=6) to assess PSE was the Parenting Sense of Competence Scale, 9,12,13,17,19,20 a domain-general parenting scale that asks parents to rate perceived sense of competence in the parenting role. Some researchers consider this scale to be consistent with self-efficacy theory because the revised version, has an Efficacy subscale where the authors noted links to self-efficacy theory, although this was not explicit by the authors of the instrument.…”
Section: Literature Review Of Conceptsmentioning
confidence: 99%
“…Several studies have shown that high levels of fatigue among mothers of infants and young children have been associated with increased parenting stress Dunning and Giallo, 2012), lowered sense of competence and satisfaction in the parenting role Dunning and Giallo, 2012), increased irritability, and frustration in the parentchild relationship Giallo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is a variable that greatly influences levels of parenting stress. (13) The study also identified other variables, such as professional activity, and number of children, which can increase parenting stress, which are closely related to tiredness and work overload. (14) Parenting stress was also one of the main causes of depressive symptoms among mothers of multiples.…”
Section: Discussionmentioning
confidence: 99%